Ultra-fast pyrolysis of lignocellulose using highly tuned microwaves: synergistic effect of a cylindrical cavity resonator and a frequency-auto-tracking solid-state microwave generator. Issue 2 (22nd November 2019) - Tsubaki, Shuntaro; Nakasako, Yuki; Ohara, Noriko; Nishioka, Masateru; Fujii, Satoshi; Wada, Yuji
Abstract : Precisely tuned microwaves facilitate rapid pyrolysis of lignocellulose. Abstract : The pyrolysis of lignocellulose facilitates the rapid production of syngas, bio-oil, and biochar. However, its low thermal conductivity and high water content result in its low heat transfer efficiency. In this study, we demonstrate the ultra-fast pyrolysis of lignocellulose using highly tuned microwaves (MWs). The efficient pyrolysis of model biomass (cellulose and alkali lignin) and real biomass (rice straw) was facilitated using a cylindrical cavity resonator and a frequency-auto-tracking solid-state MW generator without any MW susceptors as thermal media. The heating rate of cellulose using 2.45 GHz MWs was 960 °C min −1 at 40 W, which was 8-fold higher than that obtained using conventional conductive heating (120 °C min −1 ) at 100 W. The highest heating rate of 330 °C s −1 was reached when rice straw was subjected to 915 MHz MWs. Using in situ resonance frequency monitoring, the carbonisation of rice straw occurred within seconds during fast heating under MW irradiation. This study demonstrated that highly tuned MW energy could facilitate the ultra-rapid pyrolysis of lignocellulose by directly applying MW energy without using a thermal medium.